Reassessing Wādī Debayan (Wādī al-Ḍabayʿān): an important Early Holocene Neolithic multi-occupational site in western Qatar (poster) - al-Naimi, Faisal; Price, Kathryn M.; Cuttler , Richard; Arrock, Hatem (Proceedings of the Seminar for Arabian Studies, 2011)
The flint scatter site of Wādī Debayan (Wādī al-Ḍabayʿān) (Qatar National Historic Environment Record 141) is located in the north-west of Qatar and situated on the former Holocene coastline approximately 3 m above sea level, 2.5 km from the modernday shoreline, and south of the historic walled town of al-Zubārah. The flint scatter covers an area of approximately 240 × 210 m to the north of a sediment-filled wadi, Wādī Debayan, and was discovered during survey in 2009. Initial identification of the lithic material collected during the 2010 season has yielded diagnostic artefacts of the Arabian Bifacial Tradition (ABT) and in excess of fifty sherds of ʿUbaid pottery. This suggests a Late Stone Age (Neolithic) occupation(s) of the site with a tentative date of 6000-3500 BC. An outline of the initial results is presented in this paper. The lithics are currently undergoing detailed attribute and spatial analysis, though further fieldwork and subsequent analysis is required to understand fully the exact nature, duration, and chronology of occupation(s). Further site investigations will be undertaken during the 2011 season.